Obtention of Cellulose Acetate Nanofibers From Sugar Cane Bagasse (2017)
Cellulose is one of the oldest natural polymers, it is renewable, biodegradable, and can be derivatized to manufacture useful products. The electrospinning, a technique for the manufacture of nanofibers, has garnered attention in recent years due to its versatility and potential for applications in various fields such as biomedicine, tissue engineering andalso filtration. In this study, cellulose acetate fibers have been obtained by electrospinning. To achieve these results, the cellulose was initially obtained from the sugar-cane bagasse of local plantations in Moniquira, Boyaca, then cellulose was modified to obtain cellulose acetate, which has enhanced properties for electrospinning. Yarn parameters were determined, such as needle-manifold distance, flow rate, voltage and polymer concentration, among others. Instrumentalanalyses were carried out including Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Differential Scanning Calorimetry (DSC), and Thermogravimetric Analysis (TGA). As a result, cellulose acetate fibers were obtained with an average diameter of 258 nm, with excellent properties such as temperature resistance. This was done in order to continue the work on nanofiber functionalization, as for example, cationization of cellulose and further addition ofreactive dyes.